2013
DOI: 10.1007/s11104-013-1725-x
|View full text |Cite
|
Sign up to set email alerts
|

High water users can be drought tolerant: using physiological traits for green roof plant selection

Abstract: Background and aims: Green roofs are often installed to reduce urban stormwater runoff. To optimally achieve this, green roof plants need to use water when available, but reduce transpiration when limited to ensure survival. Succulent species commonly planted on green roofs do not achieve this. Water availability on green roofs is analogous to natural shallowsoil habitats including rock outcrops. We aimed to determine whether granite outcrop species could improve green roof performance by evaluating water use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
69
2
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 112 publications
(89 citation statements)
references
References 63 publications
3
69
2
1
Order By: Relevance
“…These plants were selected as part of a larger research project due to their high transpiration rates, but also because they can tolerate long drought periods common in Melbourne summers [38]. Plant foliage coverage was quantified through photo pixel counts using Adobe Photoshop CC 2015 program.…”
Section: Experimental Green Roofsmentioning
confidence: 99%
See 1 more Smart Citation
“…These plants were selected as part of a larger research project due to their high transpiration rates, but also because they can tolerate long drought periods common in Melbourne summers [38]. Plant foliage coverage was quantified through photo pixel counts using Adobe Photoshop CC 2015 program.…”
Section: Experimental Green Roofsmentioning
confidence: 99%
“…The difference between the two roofs is likely due to the large additional amount of irrigation water retained in the thicker 200 mm green roof and its larger cooling effect is likely due to both higher evaporation from the substrate and increased transpiration from the plants. In glasshouse conditions, Farrell et al [38] found that these species increase water use according to water availability. However, due to the complexity of the evapotranspiration cooling effect of vegetated and irrigated green roofs in hot and dry climate, the authors understand that further study and research are necessary to better understand these dynamics.…”
Section: Summer Heat Fluxes Of Sparsely Vegetated Green Roofsmentioning
confidence: 99%
“…Some of the most common succulent species can have high survival rates on green roofs and commonly make up for a substantial part of the total cover, but due to their water-preserving physiological adaptations, they have rather low evapotranspiration rates and consequently a lower cooling capacity. Using plant traits to select plants from natural dryland habitats that have optimised water-use strategies for evaporation during wet periods at the same time as being drought tolerant could be a way to optimise green roof cooling capacity (Farrell et al 2013).…”
Section: Selection and Management Of Urban Vegetation Under Changing mentioning
confidence: 99%
“…Plants possess an incredible diversity of water use strategies, many of which are appropriate in green roof contexts across a range of regional climatic conditions. Farrell et al (2013a) have developed a conceptual model to screen potential plants for green roof applications based on their water use under mesic and xeric conditions as well as their ability to minimize water stress during periods of water deficit. Here I categorize a slightly broader (although still not comprehensive) list of water use strategies into syndromes that relate to green roof performance.…”
Section: Plant Water Use Strategies For Green Roofsmentioning
confidence: 99%